Stroke mechanics (7 x 50m) - Pyne, D.; Maw, G.; Goldsmith, W. (coachesinfo.com, 2000)
Swimming is a technically demanding sport and a substantial proportion of training time is devoted to the refinement of a swimmer's technique. A series of 7 x 50m swims of progressively increasing speed is used to establish the relationship between swimming velocity (V), stroke rate (SR) and distance per stroke (DPS).